Pengaruh Disiplin Kerja, Motivasi dan Lingkungan Kerja terhadap Kinerja Karyawan PT Wahyu Jaya Textile - Wahyu Subagyo; Ketut Elly Sutrisni (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
This study investigates how work discipline, work motivation, and the work environment influence employee performance at PT Wahyu Jaya Textile in Denpasar. The company faces internal challenges related to productivity and performance management, making the evaluation of these factors essential. A quantitative approach was applied using a census sampling technique, involving all 33 employees as respondents. Data were collected through an ordinal-scaled questionnaire and analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression with SPSS. The results show that work discipline and work motivation have a positive and significant effect on employee performance, indicating that consistent adherence to rules and strong internal drive contribute directly to higher performance. Meanwhile, the work environment does not show a significant effect, suggesting that variations in physical and non-physical working conditions are not the main determinant of performance within the company. The simultaneous test confirms that all three variables collectively influence performance, with an R² value of 0.660, meaning 66% of performance variation is explained by the model. These findings highlight the importance of strengthening discipline and motivation as key strategies to improve employee performance at PT Wahyu Jaya Textile.